A one-dimensional Cd(II) coordination polymer with a two-dimensional supramolecular architecture through halogen···halogen interaction. (22nd November 2017) - Xue, Li-Ping; Tao, Jing-Jing
ABSTRACT: A new cadmium coordination polymer, formulated as [Cd(L)(phen)]n, were prepared by hydrothermal reactions based on 3, 4-dibromothiophene-2, 5-dicarboxylic acid (H2 L) and 1, 10-phenanthroline (phen) mixed organic linkers. In the complex, adjacent Cd 2+ ions are linked by L 2− anions to form a one-dimensional (1D) [CdL]n chain with [Cd2 (COO)2 ] as the secondary building unit (SBU). These adjacent chains are further stacked together by direct C−Br···Br halogen bonds interactions, generating a two-dimensional (2D) supramolecular structure. From the viewpoint of topology, the 2D supramolecular network can be rationalized to a 3, 4-connected 3, 4L13 net with {4.6 2 }2 {4 2 .6 2 .8 2 } topology.